2017
DOI: 10.1016/j.envpol.2016.10.100
|View full text |Cite
|
Sign up to set email alerts
|

Micropore clogging by leachable pyrogenic organic carbon: A new perspective on sorption irreversibility and kinetics of hydrophobic organic contaminants to black carbon

Abstract: Black carbon (BC) plays a crucial role in sequestering hydrophobic organic contaminants in the environment. This study investigated key factors and mechanisms controlling nonideal sorption (e.g., sorption irreversibility and slow kinetics) of model hydrophobic organic contaminants (nitrobenzene, naphthalene, and atrazine) by rice-straw-derived BC. After removing the fraction of leachable pyrogenic organic carbon (LPyOC) (referring to composites of dissoluble non-condensed organic carbon and associated mineral … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(20 citation statements)
references
References 48 publications
1
19
0
Order By: Relevance
“…134 Changes in the intrinsic pore size distributions of pCNPs as a result of transformation and leaching of soluble phases can also affect the pCNP-contaminant binding potential. 137 Changes in water chemistry, surface functionality, and NOM loading all affect the aggregation of CNPs. 15,47,107 Changes in CNP aggregation as a result of transformation in natural environments can alter the pore structure and pore volume, thus affecting the sorption and desorption of contaminants as well as their co-transport with the CNPs.…”
Section: Effect Of Cnp Aggregation and Porosity On Contaminant Bindingmentioning
confidence: 99%
See 1 more Smart Citation
“…134 Changes in the intrinsic pore size distributions of pCNPs as a result of transformation and leaching of soluble phases can also affect the pCNP-contaminant binding potential. 137 Changes in water chemistry, surface functionality, and NOM loading all affect the aggregation of CNPs. 15,47,107 Changes in CNP aggregation as a result of transformation in natural environments can alter the pore structure and pore volume, thus affecting the sorption and desorption of contaminants as well as their co-transport with the CNPs.…”
Section: Effect Of Cnp Aggregation and Porosity On Contaminant Bindingmentioning
confidence: 99%
“…130,[140][141][142][143] In addition, interactions between CNPs and NOM can result in the blockage of micropores and mesopores, thereby trapping contaminants within these pore spaces. 132,137 Organic contaminants sorbed by CNTs, fullerenes, fossil coal, and biochar are generally not very bioaccessible because of their high contaminant-binding capacities. 116,144,145 However, when comparing these materials, which are generally produced under controlled conditions, with their counterparts from unintentional emissions (e.g., soot, 24,25 biochar produced under poorly controlled conditions, 146 or wildfire charcoal 29 ), the sorption and release of organic contaminants can differ considerably.…”
Section: Effect Of Cnp Aggregation and Porosity On Contaminant Bindingmentioning
confidence: 99%
“…For instance, it has been suggested that ageing in soil has a limited impact on the pore size distribution of some biochars ( Sorrenti et al, 2016 ; Sigmund et al, 2017a ), but it is not known whether this applies to all biochar-soil systems. Our results show that soil and compost can significantly reduce the sorption of contaminants to biochar, and it has also been shown that pore blockage can entrap sorbed contaminants and reduce their desorption potential ( Yang & Xing, 2007 ; Wang et al, 2017 ). How ageing and weathering processes affect the remobilisation of contaminants (desorption) has been relatively poorly considered up to now, although it an essential aspect impacting the long term performances of soil amendments.…”
Section: Discussionmentioning
confidence: 57%
“…In realistic settings where biochar is amended to contaminated soil, biochar is subject to a range of biological, physical and chemical processes involving its interactions with various soil components, and leaching of its most soluble fractions ( Hale et al, 2011 ; Wang et al, 2017 ). These processes can have a direct impact on the surface chemistry and porosity of biochar and the way it interacts with contaminants.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, the aromaticity of humic substances or, conversely the hydrophobicity/aromaticity ratio, seems to be a determining factor and explains much of the variability of atrazine absorption [20][21][22]. Several studies have found that the application to soil of highly aromatic organic amendments (such as humus with a high degree of maturity or different forms of fossil or pyrogenic organic matter, i.e., black carbon) has an outstanding influence on atrazine sorption [23][24][25]. In the case of alachlor, it was found that, although tillage practices did not significantly affect its sorption into the soil, biochar (highly aromatic soil amendment) increased its sorption between 4× and 33× compared to unamended soil [26].…”
Section: Introductionmentioning
confidence: 99%